2017
DOI: 10.1177/0194599817717674
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Paranasal Sinus Mucoceles: Meta‐analysis of Visual Outcomes

Abstract: Objective Paranasal sinus mucoceles are benign cystic lesions originating from sinus mucosa that can impinge on adjacent orbital structures, causing ophthalmic sequelae such as decreased visual acuity. Definitive treatment requires surgery. We present the first meta-analysis quantifying the effect of preoperative visual function and time to surgery on postoperative visual acuity outcomes. Data Sources PubMed, Ovid, Embase, Web of Science, and the Cochrane Library. Methods Two independent authors systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…Paranasal sinus mucoceles with visual disturbances are treatable diseases only if optic nerves were decompressed promptly [2]. Previous studies reported that the time to surgery and preoperative visual acuity could predict postoperative visual acuity improvement [3,4]. In the current case, we surmise that further delay of even short hours before surgery might be harmful to vision outcome since the patient's vision was severely and rapidly deteriorated.…”
Section: Discussionmentioning
confidence: 62%
“…Paranasal sinus mucoceles with visual disturbances are treatable diseases only if optic nerves were decompressed promptly [2]. Previous studies reported that the time to surgery and preoperative visual acuity could predict postoperative visual acuity improvement [3,4]. In the current case, we surmise that further delay of even short hours before surgery might be harmful to vision outcome since the patient's vision was severely and rapidly deteriorated.…”
Section: Discussionmentioning
confidence: 62%
“…In a meta-analysis of 85 reports (comprising a collective total of 207 patients) on visual disturbance involving paranasal sinus mucoceles, a time from onset to surgery of <6 days was associated with improved visual acuity outcomes, indicating the importance of early surgical intervention. 2 Moriyama et al 10 also noted that in patients exhibiting a gradual progression from mild to moderate visual disturbance, the recovery of visual acuity depends on the time from onset to surgery. In the current study, the time from onset to surgery for rhinogenous optic neuritis was identified as a significant predictor of postoperative visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Finger counting, hand motion, light perception, and no light perception cannot be represented as (d) and were calculated as 1.9, 2.3, 2.7, and 3.0, respectively, in accordance with a previous study. 2 The values were calculated to the second decimal place. Recovery of visual acuity was defined as an improvement of !2 lines in logMAR.…”
Section: Methodsmentioning
confidence: 99%
“…Paranasal sinusmucoceles are benign pseudocystictumors, they have an expansive and destructive tendency and a slow evolution. 1 All locations are possible; they are frequently found in the frontal sinus, the anterior ethmoidal sinus, the maxillary sinus, while posterior ethmoidal sinus and sphenoid sinus are rarely affected (less than 1%). 3 Ostial obstruction have been advanced to explain their etiopathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it exerts pressure on the surrounding structures. 1 Previous trauma and sinus surgery are the most common cause. Mucoceles following radiotherapy are rare.…”
Section: Introductionmentioning
confidence: 99%